Stem Cell Therapy in Systemic Diseases - A Literature Review - Thahaseen M; Kaviyah V; Ayisha Mehthaf Ismail; R.Jennifer Monisha; Osheen Fazeena Nasar; Minakshi (Journal of Medical Biomedical and Applied Sciences, 2021)
Stem cells are effective for various diseases, such as spinal cord injuries, Parkinson’s disease, Alzheimer’s disease, cerebral ischemia, myocardial infarction, muscular dystrophy, diabetes, liver diseases, eye diseases, immune diseases, and oral diseases. DPSCs have the potential for use in a cell-therapeutic paradigm shift to treat these diseases. It has also been reported that DPSCs have higher regenerative potential than the bone marrow-derived mesenchymal stem cells known as representative MSCs. Therefore, DPSCs have recently gathered much attention. In this review, the therapeutic potential of stem cells, the latest progress in the pre-clinical study for treatment of these various systemic diseases, and the clinical applications of stem cells in regenerative medicine, are all summarized.